Gamified Shoulder Rehabilitation for Mild Stroke Patients Using Virtual Reality - Roy Francis Navea; Vincent Mao Talde; Francisco Luis Armintia; Sarrah Mae Dela Cruz; Gabriel Medina; Alvin Decena (International Journal of Technology)
Stroke patients often encounter upper extremity impairments that necessitate rehabilitation. Traditional motor rehabilitation methods may struggle with patient adherence due to low engagement. This lack of engagement can lead to decreased motivation and, consequently, reduced participation in the rehabilitation process, which may impact the overall effectiveness of the treatment. Gamification in virtual reality (VR) adds game-like features to enhance engagement and motivation, thereby significantly improving patient involvement in rehabilitation. This study introduces i-Suksok, a VR-based game specifically designed for shoulder rehabilitation in mild-stroke patients. Created in the Unity platform, the game presents users with the challenge of maneuvering a round peg into specific holes on a pegboard using shoulder movements. It encompasses two modes: "Levels," which progressively increase in difficulty and adapt to the patient's shoulder range, and "Time Trial," where players aim to hit as many targets as possible within a designated time limit. The feedback and evaluation results from participants showed that, on average, 75% agreed with the metrics used, underscoring the significance of participant feedback and involvement in effective rehabilitation therapies, while perceptions of effectiveness, which influenced motivation and adherence, highlighted the importance of enhancing user experience in VR rehabilitation for better recovery outcomes which is supported by 69% of participant’s agreement. Gamification in VR has the potential to transform traditional methods in healthcare, education, training, and entertainment by providing an engaging, interactive experience that captures users' attention and fosters positive outcomes.